Dinamika Populasi Kumbang Koksi Predator (Coleoptera: Coccinellidae) pada Sistem Tumpang Sari Cabai Rawit dengan Kacang Tanah - Eka Elistia; Bambang Supeno; Dwi Noorma Putri (Jurnal Pertanian Khairun, 2026)
This study aimed to analyze the population dynamics of predatory ladybeetles in an intercropping system of bird's eye chili and peanut. An experimental method was employed, utilizing a Completely Randomized Design (CRD) with a single factor. The treatments consisted of KC0 (no intercropping), KC1 (bird's eye chili and peanut intercropping at a 1:2 ratio), KC2 (1:3 ratio), and KC3 (1:4 ratio); each treatment was replicated five times, resulting in a total of 20 experimental units. The results showed that predatory ladybeetle populations fluctuated across all treatments during the observation period. The highest population was observed in the KC1 treatment, peaking at 2.42 individuals at 9 weeks after planting (WAP), while the lowest population was found in the KC3 treatment. The KC1 treatment (1:2 ratio of bird's eye chili and peanut) provided the most optimal habitat conditions for supporting predatory ladybeetles compared to the other treatments. The population dynamics of predatory ladybeetles were influenced by prey availability, habitat complexity, and environmental conditions within the bird's eye chili and peanut intercropping system.